Models for intercultural collaboration and negotiation - Gelfand, Michele; Abbe, Allison; Sycara, Katia (Advances in Group Decision and Negotiation, 2013)
With increasing globalization of business and science, cultural differences of the parties are an important factor that affects the process and outcomes of collaborative and self-interested interactions. The social science literature on culture, human collaboration and negotiation is mostly devoted to work within the same culture. Computer science and Artificial intelligence researchers have developed computational models of cooperation, conflict resolution and negotiation without paying a great deal of attention to identifying and modelling cultural factors. The interest in understanding inter-cultural interactions has increased substantially and has led to greater interest of social scientists and computational scientists in theoretical and experimental analysis of inter-cultural exchanges, modelling and support. The aim of this volume is to bridge the gap and bring these communities together to share research work and experiences, discuss ideas and forge interdisciplinary collaborative relations.